WORK MOTIVATION IN INCREASING EMPLOYEE PRODUCTIVITY IN THE TOLINGGULA DISTRICT OFFICE - Hunawa, Robby (Public Policy Journal, 2023)
This article aims to analyze and describe work motivation in increasing employee productivity in the Tolinggula District Office. The method used in this article is a qualitative descriptive method. This method refers to the identification or characteristics that distinguish groups of people, objects and events. Data analysis used in qualitative research is an interactive model analysis consisting of three components of analysis namely: 1) Data reduction; 2) Data Presentations; 3) Data Verification and Conclusion Drawing. The results of the study show that: 1) Employee knowledge in increasing employee work productivity has been effective. This is due to the motivation given by the leadership of the Tolinggula District Office to direct employee performance in a more productive direction; 2) Employee skills in increasing employee work productivity show that they are not optimal enough. This is due to the influence of the work environment which does not encourage employees to maximize work ethics and good creativity for organizational progress; 3) The ability of employees to increase employee work productivity has shown to be quite effective. This is due to good communication between leaders and staff employees so as to motivate employees to carry out tasks in accordance with organizational goals.